2017
DOI: 10.4149/bll_2016_112
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors detection in chronic thromboembolic pulmonary hypertension, a tool for risk quantification?

Abstract: BACKGROUND: Chronic thromboembolic pulmonary hypertension (CTEPH) is characterized by chronic thromboembolic obstruction in the pulmonary bed. The defi nitive pathogenesis remains incompletely explained, although multiple risk factors of CTEPH have been identifi ed. The purpose of the study was to evaluate the risk profi le of patients with CTEPH and the representativeness of risk factors, identify possible new CTEPH risk factors and specify the epidemiology of CTEPH in our country. METHODS: In 81 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
1
6
1
Order By: Relevance
“…Based on laboratory measurements, further 4.8% of patients were identified with thyroid dysfunction resulting in a total proportion of 28.9% of patients with either thyroid disease or dysfunction. The observed prevalence of CTEPH patients receiving THR therapy was comparable to previous studies (ranging from 8.4% to 19.9%; [11,13,19,20,32]). Interestingly, hypothyroidism was independently associated with a diagnosis of CTEPH during followup (OR 4.3, 95% CI 1.4-13) in 772 patients with acute PE [12].…”
Section: Prevalence Of Risk Factors For Ctephsupporting
confidence: 88%
See 2 more Smart Citations
“…Based on laboratory measurements, further 4.8% of patients were identified with thyroid dysfunction resulting in a total proportion of 28.9% of patients with either thyroid disease or dysfunction. The observed prevalence of CTEPH patients receiving THR therapy was comparable to previous studies (ranging from 8.4% to 19.9%; [11,13,19,20,32]). Interestingly, hypothyroidism was independently associated with a diagnosis of CTEPH during followup (OR 4.3, 95% CI 1.4-13) in 772 patients with acute PE [12].…”
Section: Prevalence Of Risk Factors For Ctephsupporting
confidence: 88%
“…Furthermore, in a retrospective study comparing 433 CTEPH patients with 254 patients with pulmonary arterial hypertension, blood group non-0 was associated with CTEPH (OR 2.0, 95% CI 1.1-3.9) [10]. In the present study, 80.7% of patients with CTEPH had blood group non-0 -a slightly higher prevalence than previously reported (ranging from 67.3 to 76.0%; [11,19,21]) and considerably higher compared to the reported prevalence of 59.0% of blood group non-0 in the general population in Germany.…”
Section: Prevalence Of Risk Factors For Ctephcontrasting
confidence: 43%
See 1 more Smart Citation
“…40 Furthermore, 77% of patients with CTEPH were found to have non-O blood groups, which may be associated with increased VWF levels. 109 Although venous thromboembolism populations are also associated with elevated VWF levels which are for non-O blood groups, 110 VWF levels were higher in CTEPH relative to acute PE. 104…”
Section: Vwf In Inflammationmentioning
confidence: 97%
“…The majority of patients included were from Europe and there was an equal distribution between genders. All trials reported the prevalence of splenectomy in patients with CTEPH, but three observational studies [23][24][25] did not report the incidence of splenectomy between the CTEPH group and the PAH or thromboembolism disease (venous thromboembolism or pulmonary embolism) group, so only the prevalence of splenectomy in patients with CTEPH was included. Only two trials reported the causes of splenectomies.…”
Section: Study Identification and Selectionmentioning
confidence: 99%